Komunikasi Pembangunan dalam Mengakomodir Partisipasi Masyarakat terhadap Kebijakan Alih Fungsi Lahan Hijau - Krisnha Putu; Ni Luh Yulyana Dewi (Jurnal Penelitian Sosial Ilmu Komunikasi, 2026)
Abstract The mounting pressure of urban development has driven an alarming rate of green land conversion across major Indonesian cities, including Denpasar. Underlying this phenomenon is a fundamental problem in spatial policy communication, which tends to operate in a one-directional manner and frequently disregards meaningful community involvement in decision-making processes. This study analyzes development communication practices and community participation in green land conversion policies in Denpasar City. The research employs a qualitative method with a descriptive-interpretive approach, conducted in areas experiencing changes in green space function. Informants consisted of local government officials, community figures, landowners, and affected residents selected through purposive sampling. Data were collected through in-depth interviews, non-participatory observation, and documentation studies, then analyzed using thematic analysis. The findings reveal that green land conversion is driven by economic pressure, weak regulatory implementation, and limited dialogue between the government and the community. Policy communication tends to be one-directional, resulting in minimal public participation that occurs only after decisions have been made. These findings underscore the need to strengthen transparent and participatory development communication in order to sustain green spaces and improve urban spatial governance in Denpasar.